PEMBUATAN KNOWLEDGE MANAGEMENT SYSTEM BERBASIS WEBSITE PADA ASOSIASI DOSEN INTEGRATOR DESA (ADIDES) - Bayu Baskara, Dominggo; Arman Hakim Nasution; Achmad Amin Faizal (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
One of many administrative services carried out by various lecturer associations is the announcement of various scientific collaboration activities between members. At the Asosiasi Dosen Integrator Desa (ADIDES), the process of submitting scientific collaboration activities between members is still done manually. This process is considered less effective because it takes quite a long time because it requires confirmation and manual input by the website admin for each announcement of scientific collaboration activities. Therefore, during this community service activity, a website-based knowledge management system (KMS) application was created which can be accessed independently by association members at any time. Through this website-based KMS application, it is hoped that it can become a means of communication and dissemination of information between association members and the general public who are interested in the scientific collaboration programs offered by ADIDES. The scientific collaboration in question includes: Research, Community Service, Textbook Writing, International Journals, International Conferences, or IPR Development between ADIDES members. Implementation of community service activities is divided into several stages, namely collecting data on needs, designing and creating KMS applications, as well as trial test in using website-based KMS applications. During the trial test, participants demonstrated the use of the KMS application and filled out a survey regarding the quality of the service. Based on the survey results, data was obtained that the KMS application is easy to use and the features it has are in accordance with association needs. This application is effective in creating and announcing scientific collaboration program but still requires further development. Thus, these community service activities need to be carried out on an ongoing basis to improve the quality and speed of the ADIDES work program achievement.